Amil Zakat as the Citizen Political Participant with Religious Philantrophy Face - Rayhan Aulia Prakoso; Muhammad Lukman Hakim; George Towar Ikbal Tawakkal (Journal of Local Government Issues (LOGOS), 2022)
Indonesia’s not-totally-state-centered zakat management policy makes amil zakat in Indonesia have double-identity. It’s not only as an Islamic law formalization in state level, but also as a medium for non-parties citizens' political participation in civil level. By using literatures study, this research aims to analyze head-to-head between Amil Zakat Institute (Lembaga Amil Zakat/LAZ) YASA Malang and everyday-maker. This research also aims to enrich everyday-maker perspective, because in fact there are so many Muslim social institutions which have some similarity with everyday-maker, but with some differences in their motives and characteristic of program. Everyday-maker is a new typology of citizen political participation found by Bang and Sorensen at 1999, where citizens are fixing their daily problems theirselves, instead waiting for government to fix it. However, everyday-maker starts from Danish’s upset with their government works, meanwhile LAZ YASA Malang starts from the concept of Islamic philantrophy and spirit of building lowest-level Muslim’s socio-economics independency. This research, because of the difference of motive between LAZ and everyday-maker, successfully finds some novelty rather than the previous everyday-maker researches, like one-eighth amil’s portions as the source of amil zakat salaries and government involvement in the legality. Something else that differentiates LAZ and everyday-maker is a theological value that becomes the basic, where everyday-maker works done by LAZ is based on belief about Allah’s help and grace in the movement.